Xylochrysis guttulata sp. nov., associated with Camellia sinensis in Sichuan Province, China - Xiao, Yue; Liu, Jian-Kui (Phytotaxa, 2025)
During a survey of saprobic ascomycetes associated with Camellia sinensis (tea) in Sichuan Province, China, a novel saprophytic fungus, Xylochrysis guttulata, was isolated from a dead twig. This species is morphologically distinct from other members of Xylochrysis, characterized by shorter ostioles, larger asci, smaller ascospores, and the absence of a surrounding cellular layer exhibiting a golden-yellow hue. Phylogenetic analyses based on a multi-locus dataset comprising LSU, SSU, ITS, tef1-α and rpb2 confirmed X. guttulata as a distinct lineage within Woswasiaceae (Pararamichloridiales), forming a well-supported clade sister to X. lucida and X. aquatica. A detailed morphological description, illustrations, and the phylogenetic placement of this novel species are provided.